Radiology Education For Nurses: Building Competency In Imaging Interpretation And Patient Care (Journal of Namibian Studies : History Politics Culture, 2022)
This abstract explores the significance of radiology education for nurses, emphasizing the development of competencies in imaging interpretation and patient care. As frontline caregivers, nurses play pivotal roles in various radiological procedures, necessitating a solid understanding of imaging technologies and their implications for patient safety and comfort. Key components of radiology education for nurses include fundamentals of imaging technology, imaging interpretation skills, safety protocols, patient assessment and preparation, and communication strategies. Implementing structured education programs tailored to nursing staff's needs enhances patient safety, improves the patient experience, and fosters interdisciplinary collaboration in radiological settings. This abstract underscores the importance of investing in radiology education to empower nurses and optimize patient care outcomes.